The Concept of Kufr in Leader Verses : A Comparative Interpretation Study - Muhammad, Muhammad; Barmawi, Mahral (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2023)
Group existence and orientation is highly determined by the leader, whether they are brought to the goodness, wealth and prosperity or even to destruction. Therevore, it becomes a responsibility for the whole of people ton be selective and careful in electing a leader. Leader is a main character who has uphold justive and the principle of equality for all communities which has been taught by the newspaper and a leader is the one who holds the god mandate as well. The main leardership principles are justive and waithy for every people to whom he leads. On every leader election in the rest of the year especially in Indonesia the phenomenon of political conflict is often happned. Whereas it takes the name of religion and ideology. There are several groups voiced ang tald that Islam forbid moeslem to choose kafir or non moeslem leader. A number of newspaper verses are used as theorem to lagetimate the issue and designed the propaganda verses. These verses can be are the meaning relates to leadership in Kuran there are about ten verses which almost have the same meaning and understood as the leadership verses the verses Al?- Imr?n 118, 28, An-Nis?' 144, 89, 139, AlMaidah, 51, 57 and 81 and Mumtahanah 1. In the verses that are mentioned above, at least one word that a lot of people take it as leadership verse. "That is auliy?'' which means not only leadership but also has another meaning and wahat kufur is in this dicussion, the writer will study what auliya'' means and what kufur is in those verses according to Mufasir. The thesis is a library research which collected a number of data that are related to the discussion by muktabar commentary books that have been determined such as al -manar written by Muhaamad Rasy?d Rid?', Fahrirraz? written by Muhaamad ar-Raz? Fahruddin, F??il?l? alquran written by Say?d Qthb, Al-Misbah written by Muhammad Qurasy Shihab, al-Bay?n written by Muhammad Hasbi Asydiqi and the comments from the Indonesian Department of Religion and other books that relate to the data. The data collection will be analyzed deeply and summarized in to expectation result. From the research result, it is found that accrding to mufasir the word 'auliy?' which has mufrad wal? in the leadership verse, it is not wise to take it as leadership meaning only because this word has various meanings that are close. Why the leader is called wali, because usually a leader is close to the people of the society and he often listens to all the people complaint kufur in leadership verse according to mufasir has differen commentary. There are people who said that it is real kafir but other sard as kafir attitude and they are include as the nagation image into the truth and loyalty which leads into the nagation of Allah.